Resilient Control Design for Lateral Motion Regulation of Intelligent Vehicle - Chang, Xiao-Heng; Liu, Yi; Shen, Mouquan (IEEE/ASME transactions on mechatronics, 2019)
This article studies the state-feedback resilient control problem for lateral motion regulation of an intelligent vehicle in the presence of randomly occurring uncertainties. First, the uncertain disturbance in an external yaw moment is compensated by the randomly occurring uncertainty when modeling the vehicle system, and a resilient controller by considering the randomly occurring uncertainty is developed, which is a more general case, but increases complexity of regulation design. Then, the resilient control condition is proposed to guarantee the sideslip angle and yaw rate satisfying the prescribed H ∞ and L 2 - L ∞ performance indexes. Moreover, H ∞ and L 2 - L ∞ performance indexes of control outputs are merged into one linear matrix inequality. Finally, an illustrative simulation is given to show the effectiveness of the proposed resilient control design.